Leadership wisdom from the monk who sold his Ferrari the 8 rituals of visionary leaders : a fable - Sharma, Robin S. (Carlsbad Hay House, 2003)
Enthusiastically embraced by leading organizations such as Microsoft, FedEx, Nortel Networks, IBM, General Motors, and Arthur Andersen, Leadership Wisdom from the Monk Who Sold His Ferrari is one of the most innovative, effective, and remarkable books you will ever hear on the topic of showing leadership in your work and within your life.
Keywords: Leadership